Diffuse Midline Glioma (H3K27M mutant) in Adult: A Diagnostic Challenge - Paul, Sonal; Gadgil, Nitin M; Chaudhari, Chetan (Annals of Pathology and Laboratory Medicine, 2020)
Introduction: Diffuse midline glioma (DMG), H3K27M mutant is an infiltrative midline high grade glioma with predominantly astrocytic differentiation and K27M mutation in either H3F3A or HIST1H3B/C. Case Report: A 45-year-old female presented with complaints of headache and memory loss for 3 months. MRI was suggestive of an infiltrative mass lesion in the quadrigeminal plate cistern suggestive of pineal neoplasm. Squash and histomorphology showed a low-grade astrocytic tumour with infiltrative growth pattern. Microvascular proliferation and necrosis were absent. Immunohistochemistry showed loss of ATRX protein, focal positivity for p53 proteinand IDH1R132H negativity. On molecular analysis, H3K27M mutation was noted and the case was labelled as DMG H3K27Mmutant (WHO IV) Conclusion: DMG (H3K27M) is a newly added entity in the WHO 4th revised editionof 2016. It presents with a diagnostic challenge as it has varied histomorphology, not requiring atypia, mitosis, endothelial hyperplasia and necrosis for diagnosis as Grade IV.